Improving motility and fertilization capacity of low-quality sperm of sterlet Acipenser ruthenus during storage - Xin, Miaomiao; Cheng, Yu; Rodina, Marek; Tučková, Vladimíra; Shelton, William L; Linhart, Otomar (Theriogenology, 2020)
Improvement of sperm quality with low motility by storage could ensure higher success of fertilization and maintain higher genetic diversity, especially for sturgeons, which as endangered species have limited broodstock and gametes. Sperm was collected from mature male sterlet Acipenser ruthenus and motility was evaluated using the CASA system; samples were categorized as GS 'good sperm' (>80%) or BS 'bad sperm' (<20%). Samples from both groups were incubated with seminal plasma from good- (GSP) and bad-quality sperm (BSP), respectively for 15 min, 6 h, 24 h and 96 h at 4 °C. Motility of BS incubated in GSP increased after different storage times compared to BS incubated in BSP, while the motility and velocity of GS incubated in BSP decreased compared to GS incubated in GSP. Fertilization rates were evaluated with samples stored for 15 min and 6 h post-stripping; fertilization and hatching rate of BS after incubation in GSP increased significantly compared to the BS incubated in BSP. Inorganic ion (Na+, K+, Cl-) concentrations and osmolality of BSP were significantly lower than that of GSP. These results indicated that sterlet sperm quality can be revitalized by incubation with GSP. Further, fertilization capacity of BS after incubation in GSP can reach similar levels to the good quality sperm (∼70%). Low ion concentration and osmolality in BSP may be a partial cause of low sperm quality. The current study is the first report on the capability to revitalize low quality sterlet sperm by storage in GSP.
Keywords: sperma; Motility; spermie; ryby; Seminal plasma; Sperm Motility; fertilizace; zvířata; Fertilization success; Fertilization; Fishes; motilita spermií; Male; Semen Preservation; Sperm storage; Semen; uchování spermatu; Spermatozoa; Animals; mužské pohlaví; Sturgeon